2014
DOI: 10.1186/1471-2458-14-1320
|View full text |Cite
|
Sign up to set email alerts
|

Specific genotypes of human papillomavirus in 125 high-grade squamous lesions and invasive cervical cancer cases from Congolese women

Abstract: BackgroundKnowledge on HPV prevalence and genotype distribution in HSIL and ICC is highly essential for the introduction of an effective vaccination program and appropriate epidemiological monitoring of viral ecology before and after vaccination in Congo. This study aimed to determine the specific-HPV genotypes in HSIL and ICC among women in southwestern Congo.Methods125 archival paraffin-embedded biopsy collected between 2008 and 2012 and histologically diagnosed were investigated. DNA extraction was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
4
10
2
Order By: Relevance
“…All HSIL/ICC cases were HPV positive, caused by highrisk types. Specific profile of genotypes found in these women confirms recent findings in this area in cases of paraffin biopsies from women with high-grade squamous lesions and invasive cervical cancer [Boumba et al, 2014], which is also typical of those reported in the literature [Eslami et al, 2008;Odida et al, 2008;de Sanjose et al, 2010;De et al, 2013;De Vuyst et al, 2013]. The result shows the interest that may have current vaccines in reducing HPV infections and prevent cervical cancer in Southwest of Congo.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…All HSIL/ICC cases were HPV positive, caused by highrisk types. Specific profile of genotypes found in these women confirms recent findings in this area in cases of paraffin biopsies from women with high-grade squamous lesions and invasive cervical cancer [Boumba et al, 2014], which is also typical of those reported in the literature [Eslami et al, 2008;Odida et al, 2008;de Sanjose et al, 2010;De et al, 2013;De Vuyst et al, 2013]. The result shows the interest that may have current vaccines in reducing HPV infections and prevent cervical cancer in Southwest of Congo.…”
Section: Discussionsupporting
confidence: 88%
“…This low rate could be explained by the limited number of genotypes evaluated for coinfection and not the technique used. However, the evaluated genotypes account for over 95% of the types circulating in our study population [Boumba et al, 2014]. This hypothesis makes not significant the limit caused by the number of genotypes studied for coinfection while valuing the prevalence found.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…After HPV types 16, the most commonly detected types were HPV 31 and HPV 33, followed by HPV 58, 18, 45, and 56 in the Czech Republic, or HPV 58, 51, 52, and 18 in Slovenia. According to a study by Boumba et al [9], the most common genotype in Europe was HPV 16, followed by HPV 18, 33, 45, 31, and in the world HPV 16,18,33,45,58.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen oncogenic strains of HPV associated with pre-cancerous lesions (intraepithelial with high risk) or CC have been identified (HPV 16,18,31,33,35,39,45 [9,10].…”
Section: Introductionmentioning
confidence: 99%